Measuring international technology spillovers and progress towards the European research area - Iulia Siedschlag (The Economic and Social Research Institute (ESRI), 2009)
The objective of this paper is to contribute to the development of an evidence-based system to monitor progress towards the European Research Area (ERA) and a knowledge-based economy. We start with an overview of existing theory and empirical evidence on the role of international technology spillovers on economic growth. Further, we discuss the transmission channels of international technology spillovers and barriers to international technology diffusion. Next we turn to measuring specialisation in knowledge-based sectors and geographical concentration patterns of these sectors. The remainder of this paper proposes three sets of indicators to monitor progress towards the ERA and a knowledge-based economy in relation to international technology diffusion.
Keywords: F23; F42; F43; O33; O47; 330; international technology spillovers; knowledge-intensive economy; absorptive capacity; European Research Area; Technologietransfer; Spillover-Effekt; Wirtschaftswachstum; Branchenentwicklung; Wissenstransfer; EU-Staaten